Scientific Literacy Skills Profiles of Eleven Grade Students on Reaction Rates Topic - Khumairoh, Alvin Jahwarotul; Ardhana, Ivan Ashif (Universitas Negeri Malang, 2024)
The literacy skills of Indonesian students, according to the results of the PISA (Program for International Student Assessment) report, show a low level. This is caused by assessment activities that have not promoted scientific literacy in the form of understanding reading, text, or science data. This study aims to describe the profile of high school students' scientific literacy skills on reaction rate material. The method used was descriptive quantitative. The research subjects were high school students who had received reaction rate material. The instrument used was 8 essay questions that had been validated and empirically tested with a reliability coefficient of 0.605 in the moderately reliable category. Based on the results of the study, students' scientific literacy skills obtained an average percentage value of 30.92% in the poor category. Students who have scientific literacy skills in the good category are 6%, 19% are sufficient, 45% are deficient, and 29% are very deficient. Indicator achievement of interpreting data and evidence scientifically obtained a percentage of 30%, and explaining phenomena scientifically obtained a percentage of 9%. Scientific literacy skills in chemistry, especially reaction rate material, are not only to achieve learning objectives, but also to train students in solving problems related to phenomena in everyday life.